Diagnosis of acute appendicitis based on clinical scores: is it a myth or reality? - Podda, Mauro; Pisanu, Adolfo; Sartelli, Massimo; Coccolini, Federico; Damaskos, Dimitrios; Augustin, Goran; Khan, Mansoor; Pata, Francesco; De Simone, Belinda; Ansaloni, Luca; Catena, Fausto; Di Saverio, Salomone (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work In April 2020, the World Society of Emergency Surgery (WSES) published the first update to the Jerusalem Guidelines on the diagnosis and treatment of acute appendicitis. In this review we have reported a summary of the contemporary evidence from the literature that led to the guidelines statements on the diagnostic strategies for appendicitis. Methods A systematic literature search was performed for studies published on the use of the most common clinical scores and imaging for the diagnosis of appendicitis. Results Alvarado, AIR and AAS scores are sufficiently sensitive (up to 99%) to exclude appendicitis, accurately identifying low-risk patients and decreasing the need for imaging and the negative appendectomy rates in such patients. Conversely, for young patients deemed to be at high-risk of appendicitis according to the scores, because of the high prevalence of the disease in this group of patients ( 90%), a negative imaging scan cannot rule out appendicitis. The sensitivity and specificity of CT is reported at 0.91-0.94 and 0.90-0.95. The corresponding results for US are 0.78-0.88 and 0.81-0.94, respectively. Conclusions In young patients, a high-probability score for appendicitis may be used to select patients in which imaging is not needed. When the surgeon deems diagnostic imaging is still needed to confirm appendicitis despite the patient has been scored at high-risk, a conditional CT scan strategy is advised, with CT scan performed only after a negative or equivocal ultrasound scan.